2005
DOI: 10.1002/ajh.20277
|View full text |Cite
|
Sign up to set email alerts
|

Myeloprotective effect of short‐course high‐dose methylprednisolone treatment before consolidation therapy in children with acute myeloblastic leukemia

Abstract: In our previous studies, short-course high-dose methylprednisolone (HDMP) has been shown to shorten the chemotherapy-induced neutropenic period by stimulating the CD34 + hematopoietic progenitor cells in children with acute leukemia. In this study, we investigate the role of short-course HDMP on induction of a myeloprotective effect when administered before consolidation therapy consisting of high-dose cytosine arabinoside and daunorubicin. Thirty-four consecutive newly diagnosed children with acute myeloblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The most important factors limiting the use of G‐CSF are its high cost and requirement of parenteral administration [9]. In our study, cost analysis made in groups receiving myelopoiesis‐inducing treatments revealed that the mean cost of treatment per neutropenic attack was statistically higher in the G‐CSF group than the HDMP group.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The most important factors limiting the use of G‐CSF are its high cost and requirement of parenteral administration [9]. In our study, cost analysis made in groups receiving myelopoiesis‐inducing treatments revealed that the mean cost of treatment per neutropenic attack was statistically higher in the G‐CSF group than the HDMP group.…”
Section: Discussionmentioning
confidence: 61%
“…Despite mild and temporary side effects, short‐lasting HDMP treatment is a well‐tolerated therapeutic option [6,9,24,28,29]. In our study, none of patients had intolerable side effects or infections requiring cancellation of the treatments.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations